2002
DOI: 10.1038/sj.ijo.0802144
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to endocrine disrupters: consequences of gastroplasty on plasma concentration of toxic pollutants

Abstract: BACKGROUND: Body weight loss occurring after a hypoenergetic diet or a gastroplasty could be followed by an increase in blood concentration of potentially toxic pollutants that can interfere with the hormonal system (endocrine disrupters). DESIGN: Thirty obese individuals recruited for gastroplasty were compared before and after treatment with 45 normal-weight people. MEASUREMENTS: Blood samples were analyzed for DDT, DDE, HCB and PCBs no. 28, 52, 101, 118, 138, 153 and 180, by gas chromatography -mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…If adipose tissue levels did decrease in our subjects, the associations found would underestimate the true relationship. In contrast, studies of organochlorine levels after sudden weight loss in obese individuals have reported an increase in serum and adipose levels of PCBs and other organochlorines (Charlier et al 2002;Chevrier et al 2000). This effect was not noted for chlordane-related compounds in a longitudinal study of Swedish women, where body mass index (BMI) and a recent change in weight were not associated with a difference in serum trans-nonachlor and oxychlordane levels, although these factors were associated with a difference in most serum PCB congener levels (Glynn et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…If adipose tissue levels did decrease in our subjects, the associations found would underestimate the true relationship. In contrast, studies of organochlorine levels after sudden weight loss in obese individuals have reported an increase in serum and adipose levels of PCBs and other organochlorines (Charlier et al 2002;Chevrier et al 2000). This effect was not noted for chlordane-related compounds in a longitudinal study of Swedish women, where body mass index (BMI) and a recent change in weight were not associated with a difference in serum trans-nonachlor and oxychlordane levels, although these factors were associated with a difference in most serum PCB congener levels (Glynn et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Both chemotherapy (37;38) and changes in body weight (41;46) are reported to influence blood organochlorine levels. Results from sub-analyses which excluded men treated with chemotherapy or who experienced notable weight change were similar to those from the main analysis, but we cannot rule out other unmeasured effects of either treatment or disease that could result in either differential or non-differential exposure misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…1 In response to body weight loss, OC concentration increases in plasma 2,3 and they are more susceptible to exert their adverse effects on metabolism. In this regard, the increase in OC concentration induced by weight loss has been shown to be an independent predictor of the decrease in plasma tri-iodothyronine (T 3 ), 4 resting metabolic rate, 4 and skeletal muscle oxidative enzyme activity 5 resulting from weight loss.…”
Section: Introductionmentioning
confidence: 99%